(3GdCfaS GdeCfhS ef GUWdGM UGMH GdbGehSs - (3eMeO GdMHjHs
(3ChdgG (B:s
(3bGd eMeO GdMHjH GdefJSH dYGHO GdbGOQ ecJSH CaQZJg ai bGdH GdEjLGR CfLRJ ajg CjeG EjLGR s
(3BNQgG (B:s
(3aCaQZJ ai bGdH GdEOZGe Hfbd GdgGA HGdE(B>(3ZGe cGdfbd ai UjGZI GdCFeI aefJgi Gdbhd HgG GdJJeg JeJ s
(3CQLhRI CJegG HGdbjQhGf SfI (B1234(3g`s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(7888(3g`(B) s
Keywords: (3GddZIs